A rare diaphragm in the common carotid artery: A first case report and literature review. Issue 28 (July 2017) - Wang, Ying; Li, Jian-chu; Lv, Ke; Wang, Nai-li; Sharen, Gao-wa; Tan, Li
Abstract: Rationale: We present a case of common carotid artery (CCA) diaphragm. To our knowledge, this is the first reported case in the imaging literature. Patient concerns: A 33-year-old woman presented herself to an annual health examination without any report of ill health. Diagnoses: A stenosis with aneurysm dilation on the proximal part of the right CCA was revealed on ultrasound and CTA, by which a diaphragm-like structure on the stenosis lesion was clearly identified. An anatomic variant of artery was first considered. Interventions: The patient was followed up closely. Outcomes: There was no progression of her CCA stonosis 1 year later. Lessons: This unusual and previously unreported case is presented to alert vascular sonographers and radiologists to its existence.